Melatonin Supplementation Alters Maternal and Fetal Amino Acid Concentrations and Placental Nutrient Transporters in a Nutrient Restriction Bovine Model - Rebecca Swanson; Zully Contreras-Correa; Thu Dinh; Heath King; Darcie Sidelinger; Derris Burnett; Caleb Lemley (Metabolites, 2022)
Melatonin rescues uterine blood flow and fetal body weight in a seasonal dependent manner within a nutrient restriction bovine model. We sought to identify the effects of nutrient restriction, melatonin, and sampling time on maternal and fetal amino acids, and placental nutrient transporters. Pregnant heifers received adequate or restricted nutrition, and 20 mg of melatonin or placebo from gestational days 160–240 over two seasons. On day 240 maternal and fetal blood, amnion, and placentomes were collected. Amino acid concentrations were determined by gas chromatography-mass spectrometry. Caruncle and cotyledon tissues were assessed for nutrient transporter density by qPCR. Data were analyzed using the MIXED procedure of SAS for fixed effects. In fall, melatonin rescued effects of nutrient restriction on System N, Anion, and total maternal amino acids. Furthermore, melatonin rescued effects of nutrient restriction on Systems A, N, Br, Bo, and essential amnion amino acids. In summer, melatonin rescued effects of nutrient restriction in Systems Br and Bo maternal amino acids. Furthermore, melatonin rescued effects of nutrient restriction on caruncle SLC38A10 and SLC38A2. Melatonin rescued effects of nutrient restriction in a seasonal dependent manner. These data align with previous studies suggesting melatonin is a more effective therapeutic in summer months.